Project feasibility : tools for uncovering points of vulnerability - Mesly, Olivier (Industrial innovation series., 2017)
This book presents a set of tools that will aid in deciding whether a project should go ahead, be improved, or abandoned altogether by pinpointing its vulnerabilities. It offers a review of project feasibility analysis, and more critically, psychodynamic aspects that are often neglected, including how stakeholders interact. It provides a complement to the common techniques used for analyzing technical, financial, and marketing feasibility. The goal is to identify "hidden truths" and eliminate those gray areas that jeopardize the success of a given project. The focus is on uncovering points of vulnerabilities in four key aspects of a project: People, Power, Processes, and Plan.